Are Contributors Rational? Untangling Strategies of Political Action Committees - Stratmann, Thomas (Journal of Political Economy, 1992)
Empirical public choice literature and casual observation suggest that the behavior of political action committees is remarkably unsophisticated, meaning that PACs give to those legislators who would support their interests anyway. Thus it is suggested that contributor behavior deviates from rational behavior, which is a cornerstone of economic analysis. In this paper, a switching regression model is estimated that allows for strategies of PACs to vary for different contribution recipients. I analyze the behavior of farm PACs over three election cycles. In contrast to previous findings, I find that contributor behavior is not inconsistent with rational behavior. Contributors who attempt to influence the voting behavior of members of Congress give the most money to legislators whose constituency interest suggests that they are likely to be undecided on how to vote and PACs give less money to legislators who represent districts with larger farm populations because those legislators are likely to vote in contributor interests anyway.